2007
DOI: 10.1002/ibd.20026
|View full text |Cite
|
Sign up to set email alerts
|

Expression of nonclassical class I molecules by intestinal epithelial cells

Abstract: It is well recognized that the nature of the immune response is different in the intestinal tract than in peripheral lymphoid organs. The immunologic tone of the gut-associated lymphoid tissue is one of suppression rather than active immunity, distinguishing pathogens from normal flora. Failure to control mucosal immune responses may lead to inflammatory diseases such as Crohn's disease (CD) and ulcerative colitis (UC) and celiac disease. It has been suggested that this normally immunosuppressed state may rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 66 publications
(62 reference statements)
5
53
0
2
Order By: Relevance
“…We could not detect HLA-E expression on any TCRγδ + IEL subset. In addition, HLA-E expression on TCRαβ + IELs could be increased 2- to 3-fold upon addition of rhIFN-γ ( Figure 4C), similar to what has been shown for small intestinal enterocyte-derived cell lines (6,32).…”
Section: Tcrγδ + Iels Express Nkg2a Expression Of the Inkr Nkg2asupporting
confidence: 83%
“…We could not detect HLA-E expression on any TCRγδ + IEL subset. In addition, HLA-E expression on TCRαβ + IELs could be increased 2- to 3-fold upon addition of rhIFN-γ ( Figure 4C), similar to what has been shown for small intestinal enterocyte-derived cell lines (6,32).…”
Section: Tcrγδ + Iels Express Nkg2a Expression Of the Inkr Nkg2asupporting
confidence: 83%
“…7 However, cancer cells are able to reduce the levels of these surface ligands by inducing their downregulation and/or internalization 8 and by causing them to shed their extracellular domains, thus preventing detection by immune cells. 9,10 Recently, MICA/B mRNA has been detected in normal healthy human tissues 11,12 and in adult and normal embryonic mice. 12 This finding indicates that certain post-transcriptional mechanisms may exist to prevent the translation of these mRNAs in healthy individuals, presumably to avoid autoimmunity.…”
Section: Introductionmentioning
confidence: 99%
“…In the intestine, two major lymphocyte populations exist: the intraepithelial lymphocytes (IEL) which remain associated with the basolateral membrane of the IECs, and the LPL which localize to the subepithelial lamina propria and are in contact with IECs via basolateral projections through the semi-porous basement membrane 1,2 . Previous studies from our lab suggested that IECs function as antigen-presenting cells (APCs) and, as such, can promote regulatory T-cell responses in the mucosa [3][4][5][6][7][8] . In a reverse interaction, studies by Chen et al suggested that IEL could induce IEC differentiation via the production of keratinocyte growth factor (KGF) 9 .…”
Section: Introductionmentioning
confidence: 99%